2003
DOI: 10.1038/sj.bjp.0705274
|View full text |Cite
|
Sign up to set email alerts
|

A specific taurine recognition site in the rabbit brain is responsible for taurine effects on thermoregulation

Abstract: 1 Taurine and GABA are recognized as endogenous cryogens. In a previous study, some structural analogues of taurine, namely 6-aminomethyl-3-methyl-4H-1,2,4-benzothiadiazine 1,1-dioxide (TAG), 2-aminoethylarsonic (AEA), 2-hydroxyethanesulfonic (ISE) and (7)cis-2-aminocyclohexane sulfonic acids (CAHS) have been shown to displace [ 3 H]taurine binding from rabbit brain synaptic membrane preparations, without interacting either with GABA-ergic systems, nor with taurine uptake mechanism, thus behaving like direct t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…In our previous studies [86], we demonstrated that the receptor is neither activated nor antagonized by structurally similar amino acids such as glutamate, GABA and glycine. These observations were later supported by Frosini and colleagues [87]. There is also a strong possibility of there being two types of taurine receptor; an ionotropic taurine receptor [88] and a metabotropic taurine receptor [60].…”
Section: Discussionmentioning
confidence: 77%
“…In our previous studies [86], we demonstrated that the receptor is neither activated nor antagonized by structurally similar amino acids such as glutamate, GABA and glycine. These observations were later supported by Frosini and colleagues [87]. There is also a strong possibility of there being two types of taurine receptor; an ionotropic taurine receptor [88] and a metabotropic taurine receptor [60].…”
Section: Discussionmentioning
confidence: 77%
“…However, endogenous cryogenic substance contained in urine has not been identified so far. Recently, there are several reports showing possible cryogens, such as taurine, GABA, or leukotrienes [21][22][23]. However, they are rather small molecules and may produce anapyrexia as neurotransmitters, mediators or modulators in the central nervous system.…”
Section: Known Exogenous and Endogenous Cryogensmentioning
confidence: 99%
“…Definitive identification of taurine receptors is still emerging. 20,21 Further mechanistic studies are necessary to understand the direct role of taurine receptors on propagating neurotransmission. A summary schematic depicting the mode of action of taurine as a neuroprotective agent is shown in Figure 1.…”
Section: Taurine Downregulates Key Players In the Intrinsic Apoptosismentioning
confidence: 99%
“…20 Recently, an independent report further strengthened our findings that a specific recognition site exists that is used exclusively by taurine. 21 Taurine is known for its ability to neuromodularly inhibit postsynaptic taurine receptors and act as an indirect agonist of GABAA and glycine receptors, thereby increasing the duration of chloride channel conductance. 22 Apart from this, the presence of a sodium-dependent taurine transporter (TauT) has been confirmed, and TauT knockouts demonstrate retinal degeneration, reduced olfactory sensitivity, and the manifestation of clinically important age-dependent diseases.…”
Section: Introductionmentioning
confidence: 99%